Threshold voltage modeling of Gaussian-doped Dual work function Material Cylindrical Gate-all-around (CGAA) MOSFET considering the effect of temperature and fixed interface trapped charges. (February 2022) - Banerjee, Pritha; Das, Jayoti
Abstract: Current research endeavor encompasses comprehensive threshold voltage analysis of a Gaussian-doped Dual work function Material (DM) Cylindrical Gate-all-around (CGAA) MOSFET with temperature variance in presence of fixed interface trap charges. Threshold voltage reliability over a wide range of temperature in presence of trap charges and its Gaussian-parameters such as projected range and straggle based dependencies are exhibited. Short channel response of the device has also been considered. Analytical results are corroborated through simulation outputs from Atlas.